The Effect of Phytoestrogen Compounds on Hormonal Balance in Animals - Suhrob Aminov; Kamronbek O‘rmonjonov; Ravshanbek Rasulov; Muxammadmuso Rustamov (Journal of Discoveries in Applied and Natural Science, 2026)
This article analyzes the effects of plant-derived bioactive compounds — phytoestrogens — on hormonal balance in animals. The chemical properties of phytoestrogens, their entry into the animal organism through feed, and their interaction mechanisms with the endocrine system are discussed. The positive and negative effects of phytoestrogens on growth, development, reproductive activity, and overall physiological condition in various animal species are also examined. The article evaluates the advantages and limitations of using phytoestrogens as feed additives based on scientific sources and provides recommendations for their controlled application in practice. The findings contribute to expanding the prospects of using environmentally safe and natural biologically active supplements in animal husbandry.